A novel dual template molecularly imprinted modified pencil graphite electrode and assisting it by second-order calibration to construct a novel electronic device in advance for simultaneous determination of ferritin and transferrin - Ali R. Jalalvand (Sensors International, 2023)
This work introduced a novel electronic device for simultaneous determination of ferritin and transferrin in real matrices. Here, a pencil graphite electrode was chosen as a platform and its surface was modified with multiwalled carbon nanotubes-ionic liquid and electrochemically reduced fullerene-C60. Finally, the surface of the biosensor was modified by dual template molecularly imprinted polymers which were produced by electropolymerization of 2-amino-5-mercapto-1, 3, 4-thiadiazole, and ferritin and transferrin as template molecules. To generate a square wave voltammetric signal from the biosensor to simultaneous determination of ferritin and transferrin, it was incubated into a solution having ferritin and transferrin and then, it was immersed into an electrochemical probe solution. By incubation of the biosensor with ferritin and transferrin, the pathways within its molecularly imprinted polymer layer were occupied by ferritin and transferrin therefore, it was reasonable to observe decreasing of the height of its square wave voltammetric response. Because of the nature of the square wave voltammetric data (potential shifts), incubation of the biosensor with ferritin and transferrin produced two severely overlapped peaks while incubation of the biosensor with both of them generated a single peak. Therefore, for simultaneous determination of ferritin and transferrin, the biosensor was assisted by three-way calibration with the help of second-order square wave voltammetric data which helped me to develop a very efficient electronic device for simultaneous determination of ferritin (sensitivity: 6.5 ​μA ​nM−1, limit of detection: 0.01 ​nM) and transferrin (sensitivity: 6.1 ​μA ​nM−1, limit of detection: 0.012 ​nM) in serum samples whose performance was comparable with a reference method.